Voltage Stability Improvement in Power System under Different Loadings using Fuzzy Logic Technique - Abdul Hamid, Zulkiffli; Musirin, Ismail; Rafidah Mohd Rapheal, Nor; Murtadha Othman, Muhammad; Aminudin, Norziana (International Journal of Engineering and Technology, 2019)
This paper presents a method for voltage stability improvement in power system under different loadings using fuzzy logic technique. Voltage stability assessment in present day plays a major role in planning and operation of power system. Therefore, it has become a challenging issue in maintaining a stable power system. To achieve this, a fuzzy-based model is developed for determining the amount of reactive power to be injected. The effectiveness of this approach will be examined using IEEE 57-bus test system. The test system is used to determine minimum voltage magnitude and fast voltage stability index, FVSI through load flow analysis. These data will be assigned as the inputs to the designed Fuzzy Inference System (FIS) for determining the injected percentage of reactive power. Experiment has validated the ability of the proposed technique and the improvement in terms of voltage magnitude was analyzed. The results have justified the effectiveness of the proposed technique in improving voltage stability of power system.Â Â